2013
DOI: 10.1002/pi.4634
|View full text |Cite
|
Sign up to set email alerts
|

Relaxations and chain dynamics of sequential full interpenetrating polymer networks based on natural rubber and poly(methyl methacrylate)

Abstract: The relaxations of natural rubber (NR)/poly(methyl methacrylate) (PMMA) interpenetrating polymer networks (IPNs) were studied using dynamic mechanical analysis, electron spin resonance (ESR) and solid state NMR spectroscopy. Samples with a lower concentration of PMMA in IPNs (25 wt%) showed only one relaxation, which corresponds to NR with a slight shift to higher temperature. IPNs with 35 wt% of PMMA showed very broad transitions arising from βand α-relaxations in PMMA, with the β-relaxation slightly shifted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
3
7
0
Order By: Relevance
“…In the pristine NR spectra [Figure (a)], the fast component was first observed in the spectrum recorded at 253 K. The greatest differences between the spectra of the unfilled and filled samples were visible around 273 K: for pristine NR, the slow component was still more intense than the fast one, whereas it had already almost vanished for the filled samples. At 293 K, the slow component was absent for the filled samples, yet it was still present for the pristine NR, even at 353 K. Such spectra have already been observed for NR and crosslinked polyisoprene at similar temperatures. Finally, at 403 K, the spectra of all of the samples contained only fast components.…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In the pristine NR spectra [Figure (a)], the fast component was first observed in the spectrum recorded at 253 K. The greatest differences between the spectra of the unfilled and filled samples were visible around 273 K: for pristine NR, the slow component was still more intense than the fast one, whereas it had already almost vanished for the filled samples. At 293 K, the slow component was absent for the filled samples, yet it was still present for the pristine NR, even at 353 K. Such spectra have already been observed for NR and crosslinked polyisoprene at similar temperatures. Finally, at 403 K, the spectra of all of the samples contained only fast components.…”
Section: Resultssupporting
confidence: 66%
“…The lowest value of τ R (slow) (rotational correlation time of the slow probes) was found in NC15A‐5 (∼20 ns). For comparison, the values of τ R (slow) and τ R (fast) (rotational correlation time of the fast probes) of a TEMPOL spin probe (4‐hydroxyl‐2,2,6,6‐tetramethylpiperidine‐1‐oxyl, similar in volume to the TEMPONE probe used here) incorporated at the same temperature in an uncrosslinked NR were reported as 10 and 1.8 ns, respectively …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The viscoelastic properties were studied using the DMA analysis (Rheometrics MK II DMA, Piscataway, NJ, USA) [ 23 ]. Measurements were taken in a tensile mode with frequency of 1 Hz and at a heating rate of 3 °C/min in the temperature interval from −85 to 170 °C.…”
Section: Methodsmentioning
confidence: 99%
“…A better understanding of polymer mixing on molecular level and phase morphology of produced blend can be done by studying the viscoelastic properties and polymer chain dynamics using electron spin resonance (ESR). In the literature, it was reported that ESR spin probes follow different environments in a given sample and are, therefore, associated to the dynamics of the host polymer [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%